Drought, warming and soil fertilization effects on leaf volatile terpene concentrations in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Penuelas, Josep; Sardans, Jordi; Llusia, Joan (Acta Physiologiae Plantarum, 2008)
The changes in foliar concentrations of volatile terpenes in response to water stress, fertilization and temperature were analyzed in Pinus halepensis and Quercus ilex. The most abundant terpenes found in both species were a-pinene and D 3 -carene. b-Pinene and myrcene were also abundant in both species. P. halepensis concentrations were much greater than those of Q. ilex in agreement with the lack of storage in the latter species (15205.60 ± 1140.04 vs. 0.54 ± 0.08 lg g -1 [d.m.]). The drought treatment (reduction to 1/3 of full watering) signiﬁcantly increased the total terpene concentrations in both species (54% in P. halepensis and 119% in Q. ilex). The fertilization treatment (addition of either 250 kg N ha -1 or 250 kg P ha -1 or both) had no signiﬁcant effects on terpene foliar concentrations. The terpene concentrations increased from 0.25 lg g -1 [d.m.] at 30C to 0.70 lg g -1 [d.m.] at 40C in Q. ilex (the non-storing species) and from 2,240 lg g -1 [d.m.] at 30C to 15,621 lg g -1 [d.m.] at 40C in P. halepensis (the storing species). Both species presented negative relationship between terpene concentrations and relative water contents (RWC). The results of this study show that higher terpene concentrations can be expected in the warmer and drier conditions predicted for the next decades in the Mediterranean region.
Keywords: fertilization; Pinus halepensis; Quercus ilex; Temperature; terpene concentration; water stress

Drought, warming and soil fertilization effects on leaf volatile terpene concentrations in Pinus halepensis and Quercus ilex - Blanch, Josep-salvador; Penuelas, Josep; Sardans, Jordi; Llusia, Joan (Acta Physiologiae Plantarum, 2008)
The changes in foliar concentrations of volatile terpenes in response to water stress, fertilization and temperature were analyzed in Pinus halepensis and Quercus ilex. The most abundant terpenes found in both species were a-pinene and D 3 -carene. b-Pinene and myrcene were also abundant in both species. P. halepensis concentrations were much greater than those of Q. ilex in agreement with the lack of storage in the latter species (15205.60 ± 1140.04 vs. 0.54 ± 0.08 lg g -1 [d.m.]). The drought treatment (reduction to 1/3 of full watering) signiﬁcantly increased the total terpene concentrations in both species (54% in P. halepensis and 119% in Q. ilex). The fertilization treatment (addition of either 250 kg N ha -1 or 250 kg P ha -1 or both) had no signiﬁcant effects on terpene foliar concentrations. The terpene concentrations increased from 0.25 lg g -1 [d.m.] at 30C to 0.70 lg g -1 [d.m.] at 40C in Q. ilex (the non-storing species) and from 2,240 lg g -1 [d.m.] at 30C to 15,621 lg g -1 [d.m.] at 40C in P. halepensis (the storing species). Both species presented negative relationship between terpene concentrations and relative water contents (RWC). The results of this study show that higher terpene concentrations can be expected in the warmer and drier conditions predicted for the next decades in the Mediterranean region.
Keywords: fertilization; Pinus halepensis; Quercus ilex; Temperature; terpene concentration; water stress